Improved Learning Outcomes of Integer Mixed Count Operations Through Cooperative Think Pair Share Model - Sri Suharti (CV. Rayyan Dwi Bharata, 2023)
This study aims to examine the extent to which the learning outcomes of class VI students at SD Negri 2 Belikurip have increased after the application of the Think Pair Share Cooperative learning model in mixed arithmetic operations with positive and negative integers. This research is a Classroom Action Research (CAR). The subjects of this study were 11 fourth grade students at SD Negri 2 Belikurip. This research was conducted in 2 cycles, each cycle held 2 meetings. the first meeting used the Think Pair Share model with group techniques, the second meeting used group techniques by giving rewards to active groups. The results of this study concluded that with the demonstration method it can be concluded: (1) learning activeness of up to 6 students or 100% in the good category; (2) The learning outcomes reach 100% or as many as 6 students have scores in the good category, with an average score of 89.3 (very good category); (3). The learning outcomes reached 83.3% 5 students had grades in the good category, with an average score of 87.5 or in the good category (B).